PROSPECTS FOR IMPROVING INTERNAL AUDIT AND FINANCIAL CONTROL OVER LABOR AND PAYMENT IN HIGHER EDUCATION INSTITUTIONS (American Journal of Business Management, Economics and Banking, 2025)
This article is devoted to the prospects for improving internal audit and financial control over labor and remuneration in higher educational institutions. The article analyzes the importance of internal audit and financial control in regulating labor relations, paying wages and maintaining accounting records in higher educational institutions. Particular attention is paid to issues such as the effectiveness of the financial control system, preventing errors in the payment of wages, and protecting the rights of employees.